Russian Economy amid the Contemporary Global Risks: Foreign Economic Aspect - A. B. Ginoyan (Vestnik MGIMO-Universiteta)
Book review: Foreign Economic Policy of Russia amid the Contemporary Global Risks. Ed. A.A. Tkachenko. Moscow. Kurs. 2019. 320 p.